Mass movement risk management database in the municipality of Coimbra and analysis of the influence of the main atmospheric conditions - Pellegrina, Georgia Jorge [UNESP]; Cunha, Lucio (Univ Coimbra, Fac Letras, 2019)
Slope instability is present in mountainous regions, and disorderly growth in urban susceptible areas, coupled with lack of land use planning, has increased the occurrence of these types of disasters in urban areas. The climatic study is necessary for the monitoring and prevention of mass movements, since they are triggered by events of extreme and / or long duration precipitation. A database is an important tool in the contribution of these studies and in risk management.
Keywords: database; mass movements; severe events; NAO; risk management